The woman painter in Victorian literature - Losano, Antonia Jacqueline (Columbus : Ohio State University Press, 2008)
"The nineteenth century saw a marked rise both in the sheer numbers of women active in visual art professions and in the discursive concern for the woman artist in fiction, the periodical press, art history, and politics. The Woman Painter in Victorian Literature argues that Victorian women writers used the controversial figure of the woman painter to intervene in the discourse of aesthetics. These writers were able to assert their own status as artistic producers through the representation of female visual artists." "Women painters posed a threat to the traditional heterosexual erotic art scenarios - a male artist and a male viewer admiring a woman or feminized art object. Antonia Losano traces an actual movement in history in which women writers struggled to rewrite the relations of gender and art to make a space for female artistic production. She examines as well the disruption female artists caused in the socioeconomic sphere. Losano offers close readings of a wide array of Victorian writers, particularly those works classified as noncanonical - by Anne Thackeray Ritchie, Margaret Oliphant, Anne Bronte, and Mrs. Humphrey Ward - and a new look at better-known novels such as Jane Eyre and Daniel Deronda, focusing on the pivotal social and aesthetic meanings of female artistic production in these texts. Each of the novels considered here is viewed as a contained, coherent, and complex aesthetic treatise that coalesces around the figure of the female painter."--Jacket
Prevailing winds and cross-currents : public discourse and the history of Victorian women painters -- Desire and feminist aesthetics in Anne Brontë's The tenant of Wildfell Hall -- Ekphrasis and the art of courtship in Jane Eyre -- Making a living : Howitt, Eliot, Oliphant -- The afterlife of Angelica Kauffman -- Disfigurement and beauty in Dinah Craik and Charlotte Yonge -- Painting the new woman : Mary Ward and the woman artist.
Includes bibliographical references (pages 267-282) and index.
Print version record.
Keywords: English fiction -- 19th century -- History and criticism; English fiction -- Women authors -- History and criticism; Art and literature -- Great Britain -- History -- 19th century; Women artists in literature; Aesthetics in literature; Feminism in literature; Art in literature; Roman anglais -- 19e siècle -- Histoire et critique; Art et littérature -- Grande-Bretagne -- Histoire -- 19e siècle.; Femmes artistes dans la littérature.; Esthétique dans la littérature.; Féminisme dans la littérature.; Art dans la littérature.; Aesthetics in literature; Art and literature; Art in literature; English fiction; English fiction -- Women authors; Feminism in literature; Women artists in literature; Great Britain; Ekphrasis; Englisch; Malerin; Roman; Engelsk litteratur -- 1800-talet -- kvinnliga författare.; Viktoriansk litteratur; Kvinnliga konstnärer i litteraturen; Englisch; 1800-1899; Geschichte 1800-1900.; Criticism, interpretation, etc; History